Solutions to the Bargaining Problem (International Journal of Engineering and Computer Science, 2014)
We briefly describe the intersection of game theory and bargaining problem as a topic of study, and explain the term Nash bargaining game. Very less work has been recorded in the field of game theory with bargaining problem. This paper presents the survey of various approaches which are used in the field of game theory with bargaining problem and elaborate the Nash bargaining game. Finally, we propose a future scope of bargaining problem in the field of zoology.